2019
DOI: 10.3390/cryst9020117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Saccharides on the Precipitation of Calcium-Vaterite Mixtures by the CO2 Bubbling Method

Abstract: Calcium carbonate is a compound existing in living organisms and produced for many biomedical applications. In this work, calcium carbonate was synthesized by a CO2 bubbling method using ammonia as a CO2 absorption promotor. Glucose, fructose, sucrose, and trehalose were added into the reaction mixture to modify characteristics of precipitated calcium carbonate particles. To determine the polymorphic form of produced calcium carbonate particles, Fourier transform infrared spectroscopy (FTIR-ATR) and X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The detailed quantitative results based on Rietveld refinement method analysis were then used for crystallite size calculation using the Scherer method [ 38 ]. Qualitative analysis of the synthesized CaCO 3 powder was carried out by comparing the vibration bending mode ratio between the vaterite phase in the 744 cm −1 area and calcite which was located at the wave number 711 cm −1 [ 39 ].
Figure 2 Space-filling representation of the crystal structure of trigonal calcite (a) and orthorhombic vaterite (b) in three dimensional lattice vectors; blue, brown and red sphere represent Ca atom, C atom, and O atom.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed quantitative results based on Rietveld refinement method analysis were then used for crystallite size calculation using the Scherer method [ 38 ]. Qualitative analysis of the synthesized CaCO 3 powder was carried out by comparing the vibration bending mode ratio between the vaterite phase in the 744 cm −1 area and calcite which was located at the wave number 711 cm −1 [ 39 ].
Figure 2 Space-filling representation of the crystal structure of trigonal calcite (a) and orthorhombic vaterite (b) in three dimensional lattice vectors; blue, brown and red sphere represent Ca atom, C atom, and O atom.
…”
Section: Methodsmentioning
confidence: 99%
“…The detailed quantitative results based on Rietveld refinement method analysis were then used for crystallite size calculation using the Scherer method [38]. Qualitative analysis of the synthesized CaCO 3 powder was carried out by comparing the vibration bending mode ratio between the vaterite phase in the 744 cm À1 area and calcite which was located at the wave number 711 cm À1 [39].…”
Section: Crystal Structure Analysis and Phase Identificationmentioning
confidence: 99%
“…Although amino acids did not promote the CO 2 absorption and the formation of high supersaturation, their stabilizing effect on the vaterite was prevalent. On the other hand, the addition of sucrose into the initial solution of calcium chloride and ammonia reduced the reaction time [85]. Sucrose facilitated the absorption of CO 2 and caused the high supersaturation in the system, which promoted the creation of vaterite.…”
Section: Additivesmentioning
confidence: 99%
“…The results obtained in our experiments showed that the addition of an organic solvent to the reaction mixture reduced the proportion of vaterite in the freshly precipitated calcium carbonate particles, even when precipitation occurred faster, i.e., in the presence of isopropanol. Earlier studies on CaCO 3 precipitation by carbonation in the presence of ammonia indicated that acceleration of the CaCO 3 precipitation process promotes the formation of vaterite [15,49]. Moreover, vaterite stabilization is observed in systems containing carbamate ions, which can be formed in solutions containing ammonia or primary amines and bicarbonate ions [26,50].…”
Section: The Average Particle Size (D) [µM] Incubation Time [H]mentioning
confidence: 98%